Running patterns and force-velocity sprinting profiles in elite training young soccer players: A cross-sectional study - Zhang, Q.; Pommerell, F.; Owen, A.; Trama, R.; Martin, C.; Hautier, C. A. (European Journal of Sport Science, 2021)
The Volodalen® field method permits to classify runners into aerial or terrestrial, based on vertical oscillation, upper-body motion, pelvis and foot position at ground contact, and foot strike pattern. The present study aimed to compare the sprint running force-velocity profiles between aerial and terrestrial runners. Sixty-Four French National-Level young soccer players (28 females, 36 males) performed three trials of unloaded maximal 40m sprints. External horizontal power-force-velocity relationships were computed using a validated biomechanical model and based on the velocity-time curve. Accordingly, the participants were classified into patterns in aerial and terrestrial runners. Terrestrial runners showed a higher maximal horizontal force (F 0) (6.73 ± 1.03 vs 6.01 ± 0.94 N·kg-1), maximal horizontal power (P max) (14.04 ± 3.24 vs 12.51 ± 3.31), maximal acceleration (Acc) (6.83 ± 0.85 vs 6.26 ± 0.89 m·s-2), and maximal rate of horizontal force (RF max) (57.41 ± 4.64 vs 52.81 ± 5.69 %) compared to aerial runners. In contrast, terrestrial runners displayed a more negative rate of decrease of RF (D RF) (-11.65 ± 1.71 vs -10.23 ± 1.66 %) and slope of the Force-Velocity relationship (F-V slope) (-0.83 ± 0.11 vs -0.77 ± 0.10 N·s·m-1·kg-1) than aerial runners. The results indicate that terrestrial runners displayed more efficient force production in the forward direction and displayed more "force-oriented" F-V profiles. Nevertheless, aerial runners were more effective in maintaining a net horizontal force production with increasing speed. Our results suggest that terrestrial runners could be more adapted to the specific short distance and high acceleration sprints running.